Study on safety assessment methods of gravity anchors based on a simplified mechanical model - Li, Hongru; Yang, Min; Yin, Xiaotao (Frontiers in Earth Science, 2023)
Gravity anchor blocks are a common type of ground anchor used for suspension bridges, whose bearing depends on its large body and gravity. As there is no stratum requirement, the safety of the anchor block is important for bridge stability. This study summarizes all available estimation indexes, calculating methods, and evaluation criteria for gravity anchor block safety for the Ruili bank of the Banjin Dam grand suspension bridge. The anti-overturning, anti-sliding, base stress, and deformation safeties were comprehensively evaluated using methods including the suggested specification method (SM), simplified mechanical method (SMM), and finite element method (FEM), the results of which were compared and analyzed. The reasons for errors and improved formulas and working conditions were presented. The main conclusions were as follows. 1) The methods for calculating different evaluation indexes according to specifications lack consistency. Moreover, FEM requires that designers have good computer skills and has low feasibility in practice. 2) The SMM for gravity anchor block safety estimation as described in this study, whose indexes cover systematic and overall, the computational formula is simple and speedy, with relatively conservative results and good practicability. 3) SM, SMM, and FEM were all used for the safety estimation of gravity anchor blocks in Ruili bank. The anti-overturning and anti-sliding stability coefficients must all meet the specification requirements of 2.0. SM cannot be used to estimate the base tensile stress under limited conditions. SMM denoted tensile stress at 2.5 times the main cable design force, compared to 3.2 P for FEM. Deformation calculation methods are not given by SM, but can be suggested by SMM based on the elastic mechanics. The horizontal displacements under design load conditions were 122 mm (SMM), 108 mm (FEM), and 44 mm (composite foundation treated by root piles), with a safety standard of <80 mm. The vertical displacements were 338 mm (SMM), 110 mm (FEM), and 123 mm (composite foundation treated by root piles), with a safety standard of <160 mm. These findings proved the feasibility of SMM for the safety design of gravity anchor blocks in cases lacking regional experience.